2022
DOI: 10.1681/asn.2022020197
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Failure Alters Parathyroid Pin1 Phosphorylation and Parathyroid Hormone mRNA-Binding Proteins, Leading to Secondary Hyperparathyroidism

Abstract: BackgroundSecondary hyperparathyroidism (SHP) is a common complication of CKD that increases morbidity and mortality. In experimental SHP, increased parathyroid hormone (PTH) expression is due to enhanced PTH mRNA stability, mediated by changes in its interaction with stabilizing AUF1 and destabilizing KSRP. The isomerase Pin1 leads to KSRP dephosphorylation, but in SHP parathyroid Pin1 activity is decreased and hence phosphorylated KSRP fails to bind PTH mRNA, resulting in high PTH mRNA stability and levels. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(303 reference statements)
0
4
0
Order By: Relevance
“…Twenty-four hours after FA-AKI induction, plasma PTH increased in the NP-FA group, in line with previous studies, which was abrogated in the LP-FA group (Figure 3A). 41,54,55 Similarly, plasma calcitriol was increased in the NP-FA group compared with the LP-FA group, which was paralleled by higher renal Cyp27b1 mRNA expression. Renal Cyp24a1 mRNA was downregulated in the NP-FA but not the LP-FA group (Figure 3, B-D).…”
Section: P I Restriction Abrogated the Aki-induced Pth-mediated Eleva...mentioning
confidence: 87%
“…Twenty-four hours after FA-AKI induction, plasma PTH increased in the NP-FA group, in line with previous studies, which was abrogated in the LP-FA group (Figure 3A). 41,54,55 Similarly, plasma calcitriol was increased in the NP-FA group compared with the LP-FA group, which was paralleled by higher renal Cyp27b1 mRNA expression. Renal Cyp24a1 mRNA was downregulated in the NP-FA but not the LP-FA group (Figure 3, B-D).…”
Section: P I Restriction Abrogated the Aki-induced Pth-mediated Eleva...mentioning
confidence: 87%
“…They found that Pin1 is expressed in ureteric bud derivatives and mediates the function of protein kinase-X (PRKX), a regulator of epithelial morphogenesis, through the WW domain of Pin1 ( Li et al, 2009 ). In contrast, Pin1 has been linked to the occurrence and progression of various kidney diseases ( Thorpe et al, 2001 ; Hassan et al, 2022a ; Patel et al, 2022 ). Genetic or pharmacological inhibition of Pin1 may help reduce renal injury by mitigating kidney fibrosis, oxidative stress, and apoptosis ( Shen et al, 2016 ; Zhao et al, 2021 ).…”
Section: Effects Of Pin1 On Kidney Diseasementioning
confidence: 99%
“…In CKD, Pin1 isomerization becomes inactive, leading to reduced Pin1-mediated dephosphorylation and conformational changes of K-homology splicing regulatory protein (KSRP). Consequently, KSRP fails to effectively bind to PTH mRNA ( Kilav-Levin et al, 2020 ; Hassan et al, 2022a ; Hassan et al, 2022b ). This results in decreased PTH mRNA destabilization by KSRP, whereas stabilization by adenosine-uridine-rich binding factor 1 (AUF1) increases, leading to elevated PTH mRNA levels and stability ( Kilav-Levin et al, 2020 ) ( Figure 6 ).…”
Section: Effects Of Pin1 On Kidney Diseasementioning
confidence: 99%
“…Secondary hyperparathyroidism (SHP) is a common complication of chronic kidney disease (CKD) that correlates with patient morbidity and mortality (1,2). In experimental SHP, the increase in PTH gene expression is attributed to posttranscriptional mechanisms due to enhanced PTH mRNA stability (3)(4)(5). An additional layer of post-transcriptional control is mediated by microRNA (miRNA).…”
Section: Introductionmentioning
confidence: 99%